Influence of spectral properties of light sources on perceived and recorded images - Kusznier, Jacek (Photonics Letters of Poland, 2021)
The text presents differences between the mechanism of seeing and recording images and potential sources of errors in color reproduction in recorded images. The measurements show that despite the relatively high values of indices (Ra, Rf i Rg) not all tested lamps are suitable for use on a photo set, as indicated by the value of TLCI index. The lighting requirements on a film set prioritize the quality of color reproduction, even at the expense of reducing the Luminous efficacy of a source (LES ) value. Full Text: PDF References L.T. Sharpe, A. Jagla, W. Jägle, "A luminous efficiency function, V*(λ), for daylight adaptation", J. Vision 5(11), 948 (2012) DirectLink K. Mangold, J.A. Shaw, M. Vollmer, The physics of near-infrared photography, Eur. J. Phys. 34 (2013), pp. 51-71 CrossRef Simunovic M. P., On Seeing Yellow The Case for, and Against, Short-Wavelength Light-Absorbing Intraocular Lenses, Archives of Ophthalmology, vol. 130, no. 7, pp. 919-926, 2012 CrossRef M. Gilewski, The ecological hazard of artificial lighting in greenhouses, Phot. Lett. Pol., vol. 11 Issue: 3, pp. 87-89, 2019. CrossRef M. Gilewski, The role of light in the plants world, Phot. Lett. Pol., vol. 11, no. 4, pp. 115-117, 2019 CrossRef I. Fryc and E. Czech Spectral correction of the measurement CCD array, Optical Engineering 41(10), pp.2402-2406 (2002). CrossRef L. Bellia, U. Blaszczak, F. Fragliasso, L. Gryko, Matching CIE illuminants to measured spectral power distributions: A method to evaluate non-visual potential of daylight in two European cities, Solar Energy, Volume 208, 2020, Pages 830-858 CrossRef J. Kusznier and W. Wojtkowski, Impact of climatic conditions on PV panels operation in a photovoltaic power plant, IEEE, 2019 15th Selected Issues of Electrical Engineering and Electronics (WZEE), Zakopane, Poland, pp. 1-6, 2019 CrossRef J. Kusznier and W. Wojtkowski, Impact of climatic conditions and solar exposure on the aging of PV panels, IEEE, 2019 15th Selected Issues of Electrical Engineering and Electronics (WZEE), Zakopane, Poland, pp. 1-6, 2019 CrossRef J. Fan, Y. Li, I. Fryc, C. Qian, X. Fan and G. Zhang, Machine-Learning Assisted Prediction of Spectral Power Distribution for Full-Spectrum White Light-Emitting Diode, in IEEE Photonics Journal, vol. 12, no. 1, pp. 1-18, Feb. 2020, Art no. 8200218, CrossRef M. Gilewski, L. Gryko, A. Zajac, Digital controlling system to the set of high power LEDs, Proc. of SPIE, 8902, 89021D, 2013 CrossRef J. Kusznier, W. Wojtkowski, Spectral properties of smart LED lamps, Phot. Lett. Pol., vol. 12, no. 1, pp. 16-18, 2020. CrossRef J. Kusznier, Changes in the Spectral Power Distribution of Light Sources for Smart Lighting, IEEE, 14th WZEE, pp. 1-5, 2018 CrossRef H. F. Ivey, Color and Efficiency of Luminescent Light Sources, J. Opt. Soc. Am. 53, 1185-1198 (1963) CrossRef F. Zhang, H. Xu, Z. Wang, Optimizing spectral compositions of multichannel LED light sources by IES color fidelity index and luminous efficacy of radiation, Appl. Opt. 56, 1962-1971 (2017) CrossRef T. W. Murphy Jr., Maximum spectral luminous efficacy of white light, Journal of Applied Physics 111, 104909 (2012) CrossRef Po-Chieh Hung and Jeffrey Y. Tsao, Maximum White Luminous Efficacy of Radiation Versus Color Rendering Index and Color Temperature: Exact Results and a Useful Analytic Expression, J. Display Technol. 9, 405-412 (2013) CrossRef V. M. Lisitsyn, V. S. Lukash, S. A. Stepanov, and Ju Yangyang , White LEDs with limit luminous efficacy, AIP Conference Proc 1698, 060008 (2016) CrossRef J. Kowalska, I. Fryc, Colour rendition quality of typical fluorescent lamps determined by CIE Colour Fidelity Index and Colour Rendering Index, Przeglad Elektrotechniczny R. 95(7), pp. 94-97, 2019 CrossRef I. Fryc, J. Fryc, A. Wasowski, "Rozważania o jakości oddawania barw źródeł światła, wyrażanej wskaźnikiem Ra (CRI), uwzględniające fizjologię widzenia oraz zagadnienia techniczno-prawne", Przeglad Elektrotechniczny R. 92(2), 218 (2016) CrossRef TECH 3353, Development of a "standard" television camera model implemented in the TLCI-2012, Source: FTV-LED, EBU, Geneva November 2012 DirectLink TECH 3354, Comparison of CIE colour metrics for use in the television lighting consistency index (TLCI-2012), Source: FTV-LED, EBU, Geneva November 2012 DirectLink TECH 3355, Method for the assessment of the colorimetric properties of luminaires the television lighting consistency index (TLCI-2012) and the television luminaire matching factor (TLMF-2013), Source: FTV-LED Geneva March 2017 DirectLink J. Kusznier, Mixing colours inside the optical fibre elements, Przeglad Elektrotechniczny, R 84(8), pp 182-185, 2008 DirectLink